Safety study of carboxymethylated Basella alba mucilage: a subchronic oral toxicity evaluation in Wistar albino rats - Chowdhury, Moumita; De, Pintu Kumar; Maji, Himangshu Sekhar; Das, Dibya (Creative Pharma Assent, 2024)
Background: The evaluation of toxicity is of paramount importance in the screening of a new compound. Basella alba mucilage possesses a versatile excipient property that can be innovated with its chemical modification to get the functionalized mucilage. A few pharmacological activities of Basella alba mucilage have also been reported earlier, but its toxicity study in rats has yet to be discussed. Aim: The study aims to assess the in vivo toxicity of carboxymethylated Basella alba mucilage in Wistar albino rats for 28 days. Material and Methods: In the current investigation, Carboxymethylated Basella alba mucilage is taken, and its subchronic toxicity study is carried out in forty-eight healthy rats (twenty-four male rats and 24 female rats), divided into four groups containing six rats of each sex. All the biochemical and hematological parameters and histopathological investigation were estimated for all the animal groups. Result: The subchronic toxicity study reveals that the modified mucilage is safe for all doses (20mg/kg body weight, 40mg/kg body weight, 80 mg/kg body weight). The study showed no significant difference in the dose group's behavioral toxicity, nephrotoxicity, and hepatotoxicity compared to the control. All the hematological and biochemical parameters lay in the normal range. The histopathological examination of treatment groups showed no abnormality or lesion in the tissue samples of internal organs. Conclusion: The study confirms the safety of Carboxymethylated Basella alba mucilage for use in pharmaceutical formulations.